Prediksi Financial Distress Pada Perusahaan Listed di Indonesia Akibat Pandemi Covid-19 - Khoerul Umam; Dwi Ratmono (Politeknik Ganesha Medan, 2023)
The purpose of this study is to examine the financial distress of companies before and during the Covid-19 pandemic. The research sample is all public companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2021. Data is collected from company annual reports with the IDX database, the number of samples is determined using the Slovin formula approach and sampling uses a stratified random sampling technique based on the type of industry . The Z-Score value was then analyzed using a different test with paired sample t-test. The results of this study show that the financial distress of IDX listed companies did not change significantly before and during the Covid-19 pandemic, except for the Consumer Non-Cyclicals sector. This finding also shows that these companies are able to adapt to the pandemic. Besides that, the market value of their equity is also able to survive on the stock exchange. This study contributes to the prediction of financial distress related to the Covid-19 pandemic to stakeholders, especially investors as material for investment considerations during a pandemic or crisis caused by other causes. The government can also use the results of this research as a reference in making policies during a pandemic. This finding also complements previous studies, which have examined the effects of pandemic conditions on company conditions.